HUTANG DAN PROFITABILITAS PERUSAHAAN (Studi Pada Perusahaan Real Estate dan Property yang Listing di Bursa Efek Indonesia) - Putri Laksono, Erica Damayanti; Demi Pengestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2018)
This study was aimed to test the effect of debt to firm profitability. Dependent variable is firm profitability proxy by return on asset (ROA), independent variable is debt consist of short-term debt (STD), long-term debt (LTD) and debt to equity ratio (DER). While control variables consist of growth and liquidity. The population of this study is real estate and property companies listed in Indonesian Stock Exchange from 2012-2016. Sampling method used in this study is purposive sampling. Data from 36 companies was taken as study samples. The method of this study is using multiple regression model with signification at 5%.The result of this study showed that short-term debt, long-term debt, and debt to equity ratio have a negative significant effect to firm profitability (ROA). While as control variables, growth and liquidity found has a positive significant effect to firm profitability (ROA). Adjusted R square obtained from this study is 0.257. This indicates that 25,7% of the dependent variable which is firm profitability (ROA) can be explained by the three independent variables are short-term debt (STD), long-tem debt (LTD), debt to equity ratio (DER) and two control variables are growth and liquidity, while the remaining 74,3% is explained by the others variable than this model.